Leaf Morphology and Anatomy of Sonneratia alba Growing at Different Salinity Habitat in Pangandaran Coastal, West Java - Rahma Fadia Haya; Rusdi Hasan; Suparman (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
Mangrove ecosystems are coastal ecosystems strongly influenced by salinity, which affects plant adaptation. Pangandaran Regency has mangrove areas with different salinity conditions that may influence the morphological and anatomical characteristics of Sonneratia alba Sm. This study aimed to analyze leaf area and thickness, stomatal characteristics, trichomes, chlorophyll content, and salt accumulation in Sonneratia alba leaves from Bulaksetra and Bojongsalawe. A qualitative and  quantitative approach was used through leaf morphological and anatomical analysis, as well as measurements of chlorophyll content and salt concentration. The results showed that leaf area and thickness did not differ significantly between locations. Stomatal density was significantly lower under high salinity (28.841 cells/mm²) compared to low salinity (40.765 cells/mm²) (p = 0.024), and chlorophyll content was also lower under high salinity (32.167 CCI) compared to low salinity (47.333 CCI) (p = 0.011). Unicellular non-glandular trichomes were found on the adaxial leaf surface of Sonneratia alba, helping reduce water loss and light exposure. Salt accumulation was higher under high salinity as an adaptive mechanism to maintain osmotic balance and reduce toxicity. Sonneratia alba shows ecophysiological plasticity in response to salinity through physiological and anatomical adjustments, especially in stomata and chlorophyll content. These findings highlight the importance of adaptive mechanisms Sonneratia alba for mangrove conservation and rehabilitation in coastal areas.